GREEN GROWTH OR ECOLOGICAL COMMODIFICATION: DEBATING THE GREEN ECONOMY IN THE GLOBAL SOUTH. Issue 3 (September 2014) - Brown, Ed; Cloke, Jonathan; Gent, Danielle; Johnson, Paul H.; Hill, Chloe
ABSTRACT This article examines recent institutional thinking on the green economy and the implications of official understandings and structuration of a green economy for the global South. Assertions about the transformative potential of a green economy by many international actors conceals a complexity of problems, including the degree to which the green economy is still based on old fossil economies and technical fixes, and the processes through which the green economy ideation remains subject to Northern economic and technical dominance. The article places the intellectual roots of the green economy within a broader historical context and suggests some ways the strategic economic and ideological interests of the global North remain key drivers of green‐economy thinking. The analysis is substantiated through two illustrative Latin American examples: the Mesoamerican Biological Corridor and green economy initiatives in Brazil. These suggest that, if the green economy is to address global challenges effectively, it must be conceptualized as more than a bolt‐on to existing globalizing capitalism and encompass more critical understandings of the complex socio‐economic processes through which poverty is produced and reproduced and through which the global environment is being transformed, a critique which also applies to mainstream discourses of sustainable development.